Phytochemical analysis of selected tropical fruits (averrhoa carambola L). and pomelo (citrus maxima) - Kong, Hui Sam (2013)
Averrhoa carambola L. (Starfruit) and Citrus maxima (Pomelo) are common tropical fruits found in Malaysia. Fruits are well known as a rich source of phytochemicals, which acts as defense system against diseases (Morton, 1987). Both the fruits were purchased from fruit stall of morning market of Jeli, Kelantan. The phytochemical analyses of all fruit extracts were performed on Shimadzu HPLC System equipped with Diode Array Detector (DAD). Most of the extracts exhibited the presence of phenolic acids, flavonoids, terpenoids, saponins and glycosides except alkaloids and chalcones. In HPLC analysis of A. carambola L. extracts vanillic acid (4.541 %) and quercetin (65.65 %) were detected as major phenolic acid and flavonoid, respectively. The C. maxima fruit extracts exhibited the presence of highest amount of 4-hydroxy-3-methoxycinnamic (1.036 %) among phenolic acids. While quercetin identified as major flavonoid in both aqueous and ethanolic extracts of C. maxima with precentage area 35.922 % and 38.734 %, respectively. The flavonoid myricetin was detected only in ethanol extracts of both the fruits with maximum amount in A. carambola L. (1.772 %). Thus, based on these findings the present study supports the high nutritional and medicinal value of the A. carambola L. and C. maxima fruits because of the presence of phenolic acids and flavonoids. Hence these fruits can be recommended for consumption to maintain general health due to the reported antioxidant properties of detected polyphenolics.